1989
DOI: 10.2131/jts.14.supplementii_1
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity Studies of Propiverine Hydrochloride

Abstract: Acute toxicity studies of propiverine hydrochloride (P-4) were carried out in mice, rats and dogs of both sexes. 1. The LD50 values of P-4 were as follows: Mice; 410 (male) and 323 (female) mg/kg in oral route, 223 (male) and 283 (female) mg/kg in subcutaneous route and 36 (male and female) mg/kg in intravenous route, Rats; 1000 (male) and 1092 (female) mg/kg in oral route, 1632 (male) and 1411 (female) mg/kg in subcutaneous route, and 22 (male) and 25 (female) mg/kg in intravenous route. On the LD50 values, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Taken together, our study indicates that Propiverine-N-oxide was also found to be the major metabolite formed in rats when administered orally, thus suggesting a similar pharmacological handling in humans and rats (Yamada et al 2010). In order to attain drug approval for propiverine in Japan and later in the EU, preclinical testing was carried out in mice, rats and dogs (Inoue et al 1989;Kohda et al 1989;Nakano et al 1989;Yamashita et al 1989Yamashita et al , 1990. In both the 13-and 52-week oral dosing study, rats presented with striking renal pathological changes: Propiverine treatment resulted in prominent protein accumulation in the cytosol and nuclei of proximal tubule epithelial cells Yamashita et al 1990).…”
Section: Introductionmentioning
confidence: 56%
“…Taken together, our study indicates that Propiverine-N-oxide was also found to be the major metabolite formed in rats when administered orally, thus suggesting a similar pharmacological handling in humans and rats (Yamada et al 2010). In order to attain drug approval for propiverine in Japan and later in the EU, preclinical testing was carried out in mice, rats and dogs (Inoue et al 1989;Kohda et al 1989;Nakano et al 1989;Yamashita et al 1989Yamashita et al , 1990. In both the 13-and 52-week oral dosing study, rats presented with striking renal pathological changes: Propiverine treatment resulted in prominent protein accumulation in the cytosol and nuclei of proximal tubule epithelial cells Yamashita et al 1990).…”
Section: Introductionmentioning
confidence: 56%